Anyone who had a heart my life and music - Bacharach, Burt 1928-2023; Greenfield, Robert (HarperCollins, 2013)
Over the past six decades, Burt Bacharach's songwriting has touched millions of listeners all over the world. Here, Bacharach steps out from behind the music to give an honest, engaging look at his life...from his work with Hal David, Dionne Warwick, Elvis Costello and many others, to his tumultuous marriages and the devastating fate of his beloved daughter. Growing up in Forest Hills, NY, during the 1930s and 1940s, Bacharach fell in love with music after sneaking into a Manhattan club to see the legendary Dizzy Gillespie. After a stint in the Korean War, he toured the world with Marlene Dietrich, wrote an endless string of hits, scored numerous Hollywood films, married movie star Angie Dickinson, and composed the music for the Broadway hit Promises, Promises. While he soared professionally, Bacharach's private life was dominated by the never-ending search for love...and the heartbreak that comes when it is lost...which is reflected in his greatest songs...From publisher description